Towards Sustainable Development Goals: Application of Hydrogen-Enriched Mahua Biodiesel/Diesel Blend to Dual-Fuel Diesel Engine - Hoang, Anh Tuan; Nayak, Swarup Kumar; Vujanovic, Milan; Guerrero-Pérez, María Olga; Rodríguez-Castellón, Enrique; López-Escalante, María Cruz; Ahmed, Shams Forruque; Hadiyanto, Hady; Luu, Van Chinh; Nguyen, Van Nhann; Nguyen, Xuan Phuong; Cao, Dao Nam (Wiley, 2025)
This study investigates the inﬂuence of hydrogen (H2 ) enrichment on the performance, combustion, and emission characteristics of a dual-fuel diesel engine operated with Mahua biodiesel/diesel blend (BDf20), in which H2 is injected into the intake manifold at ﬂow rates of 4, 6, 8, 10, and 12 L min−1 under varying engine loads. As a result, the optimum engine performance is achieved at 10 L min−1 H2 . At a peak load of 5.02 kW, BDf20 + H2 (10 L min−1 ) improves brake thermal eﬃciency (BTE) by 16.75%, and reduces brake speciﬁc fuel consumption (BSFC) by 10.83% compared to conventional diesel. For emission characteristics, unburnt hydrocarbons (HC), carbon monoxide (CO), and carbon dioxide (CO2 ) decrease by 42.65, 44.74, and 20.91%, respectively, although NOx emissions increased by 17.1% due to higher combustion temperatures. Moreover, combustion characteristics show a 9.91% rise in peak in-cylinder pressure, a 20.82% increase in heat release rate, and an 8.26% longer ignition delay period. The results conﬁrm the eﬀectiveness of H2 enrichment in improving combustion performance while signiﬁcantly reducing pollutant emissions, showing that combining H2 with biodiesel enhances the global Sustainable Development Goals (SDG) by advancing clean and renewable energy solutions.
Keywords: Hidrógeno; Biodiésel; Combustibles fósiles; Desarrollo sostenible; Hydrogen; Dual-fuel diesel engine; Biodiesel; Diesel blends